Bond characteristics, sintering behavior and microwave dielectric properties of Ce2[Zr1−x(Ca1/3Sb2/3)x]3(MoO4)9 ceramics. Issue 8 (15th April 2022) - Zhou, Xu; Ji, Xueli; Liu, Lintao; Du, Jialun; Kimura, Hideo; Zhou, Yuanyuan; Yue, Zhenxing; Wen, Jianping; Wu, Haitao
Abstract: Ce2 [Zr1−x (Ca1/3 Sb2/3 )x ]3 (MoO4 )9 (CZ1−x (CS)x M) (x = 0.02–0.10) ceramics were prepared by the conventional solid-state reaction method. The correlations between the chemical bond parameters and microwave dielectric properties were calculated and analyzed by using the Phillips–Van Vechten–Levine (P–V–L) theory. Phase composition and microstructures were evaluated by scanning electron microscopy and X-ray diffraction patterns. Lattice parameters were obtained by Rietveld refinements based on XRD data. Excellent properties for Ce2 [Zr0.96 (Ca1/3 Sb2/3 )0.04 ]3 (MoO4 )9 ceramic sintered at 775 °C: ε r = 10.68, Q × f = 85, 336 GHz and τ f = −7.58 ppm/°C were achieved.